Dominant Capital is Much More Powerful Than You Think - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2021)
How should we measure the power of dominant capital? Economists, although seldom if ever referring to `dominant capital', quantify the relative size of large firms by measuring their so-called aggregate concentration. But for all their insight, measures of aggregate concentration have one serious shortcoming: they tend to underestimate the power of dominant capital and its temporal growth – by a lot.
Keywords: P16; G3; 330; capital as power; corporate concentration; differential accumulation; dominant capital